2013
DOI: 10.1093/jxb/ert234
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen metabolism of two contrasting poplar species during acclimation to limiting nitrogen availability

Abstract: To investigate N metabolism of two contrasting Populus species in acclimation to low N availability, saplings of slow-growing species (Populus popularis, Pp) and a fast-growing species (Populus alba × Populus glandulosa, Pg) were exposed to 10, 100, or 1000 μM NH4NO3. Despite greater root biomass and fine root surface area in Pp, lower net influxes of NH4 + and NO3 – at the root surface were detected in Pp compared to those in Pg, corresponding well to lower NH4 + and NO3 – content and total N concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(146 citation statements)
references
References 101 publications
8
136
2
Order By: Relevance
“…which was largely dependent on the soil pH (DesRochers et al 2003). Luo et al (2013a) found that the different uptake abilities of NO 3 -and NH 4 ? of two contrasting poplar species were also dependent on the roots position.…”
Section: Sex-specific Difference Of Biomass Accumulation and Allocationmentioning
confidence: 98%
See 1 more Smart Citation
“…which was largely dependent on the soil pH (DesRochers et al 2003). Luo et al (2013a) found that the different uptake abilities of NO 3 -and NH 4 ? of two contrasting poplar species were also dependent on the roots position.…”
Section: Sex-specific Difference Of Biomass Accumulation and Allocationmentioning
confidence: 98%
“…can be directly assimilated into amino acids in the roots by the Glutamine synthetase-glutamate synthase (GS-GOGAT) system to form glutamine and glutamate (Dluzniewska et al 2007), whereas NO 3 -needs to be reduced to NH 4 ? by nitrate reductase (NR) and nitrite reductase (NiR) before incorporation into amino acids mainly in leaves (Rennenberg et al 2010;Nunes-Nesi et al 2010;Luo et al 2013a). Thus, ammonium ions are assimilated in the roots and transported as amino acids and amides to the leaves, while nitrate ions are transported to the leaves largely as nitrate (Arnozis and Findenegg 1986;Shelp 1987).…”
Section: Introductionmentioning
confidence: 99%
“…& Tech. Co., Ltd., Beijing, China with a backfilling solution and an ion-selective liquid cocktail as reported by Luo et al (2013aLuo et al ( , 2013b. Prior to the flux measurements, the ion-selective electrodes were calibrated by a standard solution (1 mM KCl, 0.1 mM CaCl 2 and 0.1 mM NH 4 NO 3 ) with two extra NH 4 NO 3 concentrations of 0.05 and 0.5 mM for NH 4 þ and NO 3 À , pH 5.5 and pH 6 for H þ , and O 2 concentrations of 0% and 0.21% for oxygen-microelectrode, respectively.…”
Section: Determination Of Root Morphology and Physiologymentioning
confidence: 99%
“…The fast-growing ones possess greater N and P use efficiencies and higher enzymatic activities related to N assimilation and P mobilization (Gan et al, 2015). The fast-growing broadleaved tree Populus alba  P. glandulosa is more sensitive to increasing N availability (Li et al, 2012), while the slowly growing P. popularis is more sensitive to decreasing N availability (Luo et al, 2013b). Also, fast growing P. deltoides females are more sensitive to inorganic nitrogen forms than the slow growing male trees .…”
Section: Introductionmentioning
confidence: 99%